A rubber composite material for high-performance tires and its preparation method
By using specific formulas and processes to treat nanosilica and silicate mineral powders in tire rubber materials, the problem of insufficient wear resistance and tear resistance of existing tire rubber materials is solved, and higher safety and durability are achieved.
Patent Information
- Application Number
- CN202510302304.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-14
- Publication Date
- 2025-06-03
- Estimated Expiration
- 2045-03-14
AI Technical Summary
The existing rubber materials for tires show insufficient wear and tear resistance under high load, friction and high and low temperature conditions, resulting in safety hazards.
A rubber composite material for high-performance tires is adopted, and its raw materials include nitrile rubber, styrene butadiene rubber, silicate mineral powder, nanosilica, etc. Through specific process treatment and formulation, the dispersion and bonding strength of silica in rubber are improved.
On the basis of satisfying the performance of rubber for tires, this composite material significantly improves wear and tear resistance, reduces safety hazards, and exhibits excellent fixed-extension stress under low deformation conditions.
Smart Images

Figure CN119798803B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of rubber for tires, and particularly relates to a rubber composite material for high-performance tires and a preparation method thereof. Background Art
[0002] At present, the rubber industry is one of the important basic industries of the national economy. It not only provides daily-use and medical light industrial rubber products indispensable for people's daily life, but also provides various rubber production equipment or rubber components for heavy industries such as transportation, construction, and machinery. Rubber is being more and more widely used.
[0003] As one of the most important components of an automobile, a tire mainly functions to bear the load of the automobile, ensure the friction between the wheel and the road surface, and transmit the torque of traction and braking. In recent years, with the increase in the number of automobiles, the consumption of tire rubber has been increasing. Tire rubber materials often need to be used under complex and harsh conditions, and are subjected to various squeezes, frictions, loads, and high and low temperatures during driving. The performance requirements for tire rubber materials are becoming more and more stringent.
[0004] At present, in tire rubber materials, silica is used to partially replace the conventional reinforcing agent carbon black in an attempt to reduce rolling resistance. However, the affinity between silica and rubber is poorer than that of carbon black, and the reinforcing effect is relatively poor. Although the dispersibility of silica can be improved, its reinforcing effect can be enhanced, and the rolling resistance can be reduced, the friction reduction effect is poor, and at the same time, the wear resistance, tear resistance and other properties cannot meet the requirements, which is likely to cause serious safety hazards. Summary of the Invention
[0005] The purpose of the present invention is to solve the defects existing in the prior art, and to provide a rubber composite material for high-performance tires and a preparation method thereof.
[0006] A rubber composite material for high-performance tires, the raw materials of which include, by mass: 50-100 parts of nitrile rubber, 10-30 parts of styrene-butadiene rubber, 10-20 parts of silicate mineral powder, 1-2 parts of saturated ammonia water, 5-10 parts of tetraethyl orthosilicate, 5-10 parts of amino-terminated liquid nitrile rubber, 1-5 parts of graphene oxide, 1-2 parts of carboxyl-terminated polyamide-amine, 5-10 parts of silica supported, 1-5 parts of organic bentonite, 0.1-1 part of zinc oxide, 1-3 parts of crosslinking agent, 1-2 parts of vulcanization accelerator, 1-3 parts of antioxidant, 1-3 parts of stearic acid, and 1-3 parts of dispersant.
[0007] Preferably, the silicate mineral powder is at least one of talc powder, muscovite powder, and montmorillonite powder.
[0008] Preferably, the crosslinking agent includes sulfur and organic peroxide, and the mass ratio of sulfur to organic peroxide is 2-3:0.5-1.5.
[0009] Preferably, the organic peroxide is dicumyl peroxide or / and bis(tert-butylperoxyisopropyl)benzene.
[0010] Preferably, the vulcanization accelerator is triallyl isocyanurate or / and N,N'-m-phenylene bismaleimide.
[0011] Preferably, the dispersant is sodium methylene bisnaphthalene sulfonate or triethylene glycol diisooctylate.
[0012] Preferably, the anti-aging agent is at least one of anti-aging agent BLE, anti-aging agent 445, anti-aging agent 4010, anti-aging agent DNP, and anti-aging agent TMQ.
[0013] Preferably, the silica-supported material is prepared by the following specific operations: adding zirconium acetate and yttrium acetate to water, stirring evenly, adding urea thereto, stirring at 80-90 °C for 5-10 h, centrifuging, washing, vacuum drying, adding to an ethanol aqueous solution, adding saturated ammonia water thereto and stirring evenly, adding tetraethyl orthosilicate thereto under stirring, stirring at 40-50 °C for 5-15 h, centrifuging, washing, and vacuum drying.
[0014] More preferably, the mass ratio of zirconium acetate, yttrium acetate, saturated ammonia water, and tetraethyl orthosilicate is 1-2:1-2:1-3:1-3.
[0015] The preparation method of the above rubber composite material for high-performance tires comprises the following steps:
[0016] S1. Adding the silicate mineral powder to an ethanol aqueous solution, ultrasonically treating for 1-2 h, adding saturated ammonia water thereto and ultrasonically treating for 1-2 h, adding tetraethyl orthosilicate thereto under stirring and ultrasonically treating for 1-2 h, standing for 2-6 h, filtering, washing, vacuum drying, and grinding and sieving; adding an amino-terminated liquid nitrile rubber, graphene oxide, and a carboxyl-terminated polyamidoamine, and stirring at 70-80 °C for 1-2 h to obtain a pretreated silicate;
[0017] S2. Mixing the pretreated silicate, silica-supported material, organic bentonite, zinc oxide, vulcanization accelerator, and anti-aging agent to obtain a mixture;
[0018] S3. Kneading the nitrile rubber, styrene-butadiene rubber, and the mixture for 10-20 min, the kneading temperature being 70-90 °C, adding a crosslinking agent thereto, and kneading at 160-180 °C for 1-2 h to obtain a kneaded material;
[0019] S4. Cooling the kneaded material to 110-130 °C, adding stearic acid and a dispersant in sequence and plasticizing for 10-30 min, and taking out the sheet.
[0020] Preferably, in S1, the frequency of ultrasonic treatment after adding the silicate mineral powder to the ethanol aqueous solution is 5 - 15 kHz, the frequency of ultrasonic treatment after adding saturated ammonia water is 5 - 10 kHz, and the frequency of ultrasonic treatment after adding tetraethyl orthosilicate is 5 - 10 kHz.
[0021] Beneficial effects: The present invention can improve the interfacial interaction between silica and rubber, thereby promoting the good dispersion of silica in rubber and achieving a good reinforcing effect, making the composite material not only have excellent wear resistance, but also excellent tear resistance and high hardness. When it is used in tire products, it can effectively reduce potential safety hazards.
[0022] In the present invention, nano - silica is loaded on the layered silicate mineral. Not only is the nano - silica not easy to fall off, but also it has excellent dispersibility with the amino - terminated liquid nitrile rubber, graphene oxide, and carboxyl - terminated polyamidoamine, and the binding strength between them is high. Compared with directly adding the layered silicate mineral, the product not only has excellent tear resistance, but also has excellent modulus at 100% elongation under low deformation (100%).
[0023] The present invention uses the compound doping of zirconium acetate and yttrium acetate, loads nano - silica on its surface, and is compounded with the pretreated silicate. Without adding carbon black, it has excellent reinforcing effect, while ensuring the dispersibility of silica, forming multiple cross - linking sites between the molecular chains of nitrile rubber and styrene - butadiene rubber, endowing the product with excellent wear resistance and tear resistance, and better durability than ordinary tires.
[0024] The present invention adopts a specific raw material formula and combines with a specific process to prepare a rubber composite material with wear resistance and tear resistance. On the basis of meeting the rubber performance requirements for tires, it has excellent mechanical properties, good friction reduction effect, and simple preparation method, which is suitable for large - scale popularization and application. Description of the Drawings
[0025] Figure 1 It is a comparison chart of the tensile strength and 100% modulus of the composite materials obtained in Example 5 and Comparative Examples 1 - 3.
[0026] Figure 2 It is a comparison chart of the elongation at break and tear strength of the composite materials obtained in Example 5 and Comparative Examples 1 - 3.
[0027] Figure 3 It is a comparison chart of the friction coefficient and wear rate in the dry friction wear test (load is 60 N and sliding speed is 70 mm / s) of the composite materials obtained in Example 5 and Comparative Examples 1 - 3.
[0028] Figure 4 It is a comparison chart of the friction coefficient and wear rate in the dry friction wear test (load is 140 N and sliding speed is 300 mm / s) of the composite materials obtained in Example 5 and Comparative Examples 1 - 3. Detailed implementation mode
[0029] The present invention will be further explained below in conjunction with specific embodiments.
[0030] Example 1: A rubber composite material for high-performance tires, the raw materials of which include: 50 g of nitrile rubber, 10 g of styrene-butadiene rubber, 10 g of talcum powder, 1 g of saturated ammonia water, 5 g of tetraethyl orthosilicate, 5 g of amino-terminated liquid nitrile rubber, 1 g of graphene oxide, 1 g of 3.0-generation carboxyl-terminated polyamidoamine, 5 g of silica-loaded, 1 g of organic bentonite, 0.1 g of zinc oxide, 1 g of cross-linking agent, 1 g of triallyl isocyanurate, 1 g of antioxidant BLE, 1 g of stearic acid, and 1 g of sodium methylene bisnaphthalene sulfonate.
[0031] The cross-linking agent is composed of sulfur and bis(tert-butylperoxyisopropyl)benzene in a mass ratio of 4:1.
[0032] The silica-loaded is prepared by the following specific operations: Add 1 g of zirconium acetate and 1 g of yttrium acetate to 20 g of deionized water and stir evenly. Add 1 g of urea thereto, stir at 80°C for 5 h, centrifuge, wash, vacuum dry, add to 20 g of an ethanol aqueous solution with a mass fraction of 40%, add 1 g of saturated ammonia water thereto and stir evenly, add 1 g of tetraethyl orthosilicate thereto under stirring, stir at 40°C for 5 h, centrifuge, wash, and vacuum dry.
[0033] The preparation method of the above rubber composite material for high-performance tires includes the following steps:
[0034] S1. Add talcum powder to 50 g of an ethanol aqueous solution with a mass fraction of 40% and perform ultrasonic treatment for 1 h at an ultrasonic frequency of 5 kHz. Add saturated ammonia water thereto and perform ultrasonic treatment for 1 h at an ultrasonic frequency of 5 kHz. Add tetraethyl orthosilicate thereto under stirring and perform ultrasonic treatment for 1 h at an ultrasonic frequency of 5 kHz. Let it stand for 2 h, filter, wash with deionized water, vacuum dry, and grind through a 100-mesh sieve; add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamidoamine, and stir at 70°C for 1 h at a stirring speed of 100 r / min to obtain pretreated silicate;
[0035] S2. Mix the pretreated silicate, silica-loaded, organic bentonite, zinc oxide, triallyl isocyanurate, and antioxidant BLE, and stir at a speed of 50 r / min for 10 min to obtain a mixture;
[0036] S3. Put nitrile rubber, styrene-butadiene rubber, and the mixture into a mixer and knead for 10 min at a kneading temperature of 70°C and a mixer speed of 50 r / min. Add the cross-linking agent thereto and knead at 160°C for 1 - 2 h to obtain a kneaded material;
[0037] S4. Cool the kneaded material to 110 °C, add stearic acid and sodium methylene dinaphthalenesulfonate in sequence and plasticize for 10 min, then transfer to a two-roll mill to produce sheets.
[0038] Example 2: A rubber composite for high-performance tires, the raw materials of which include: 100 g of nitrile rubber, 30 g of styrene-butadiene rubber, 20 g of talcum powder, 2 g of saturated ammonia water, 10 g of tetraethyl orthosilicate, 10 g of amino-terminated liquid nitrile rubber, 5 g of graphene oxide, 2 g of 3.0-generation carboxyl-terminated polyamide-amine, 10 g of silica-supported, 5 g of organic bentonite, 1 g of zinc oxide, 3 g of crosslinking agent, 2 g of N,N'-m-phenylene bismaleimide, 3 g of antioxidant 445, 3 g of stearic acid, and 3 g of sodium methylene dinaphthalenesulfonate.
[0039] The crosslinking agent is composed of sulfur and dicumyl peroxide in a mass ratio of 2:1.
[0040] The silica-supported is prepared by the following specific operations: Add 2 g of zirconium acetate and 2 g of yttrium acetate to 50 g of deionized water and stir evenly. Add 5 g of urea thereto, stir at 90 °C for 10 h, centrifuge, wash, vacuum dry, add to 50 g of an ethanol aqueous solution with a mass fraction of 60%, add 3 g of saturated ammonia water thereto and stir evenly, add 3 g of tetraethyl orthosilicate thereto under stirring, stir at 50 °C for 15 h, centrifuge, wash, and vacuum dry.
[0041] The preparation method of the above rubber composite for high-performance tires includes the following steps:
[0042] S1. Add talcum powder to 100 g of an ethanol aqueous solution with a mass fraction of 60% and perform ultrasonic treatment for 2 h at an ultrasonic frequency of 15 kHz. Add saturated ammonia water thereto and perform ultrasonic treatment for 2 h at an ultrasonic frequency of 10 kHz. Add tetraethyl orthosilicate thereto under stirring and perform ultrasonic treatment for 2 h at an ultrasonic frequency of 10 kHz. Let stand for 6 h, filter, wash with deionized water, vacuum dry, and grind through a 100-mesh sieve. Add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamide-amine, and stir at 80 °C for 2 h at a stirring speed of 200 r / min to obtain pretreated silicate.
[0043] S2. Mix the pretreated silicate, silica-supported, organic bentonite, zinc oxide, N,N'-m-phenylene bismaleimide, and antioxidant 445, and stir at a speed of 200 r / min for 20 min to obtain a mixed material.
[0044] S3. Put nitrile rubber, styrene-butadiene rubber, and the mixed material into an internal mixer and knead for 20 min at a kneading temperature of 90 °C and an internal mixer speed of 150 r / min. Add the crosslinking agent thereto and knead at 180 °C for 2 h to obtain a kneaded material.
[0045] S4. Cool the kneaded material to 130 °C, add stearic acid and sodium methylene dinaphthalenesulfonate in sequence and plastify for 30 min, then transfer it to a two-roll mill to make sheets.
[0046] Example 3: A rubber composite material for high-performance tires, the raw materials of which include: 70 g of nitrile rubber, 25 g of styrene-butadiene rubber, 12 g of muscovite powder, 1.7 g of saturated ammonia water, 7 g of tetraethyl orthosilicate, 9 g of amino-terminated liquid nitrile rubber, 2 g of graphene oxide, 1.7 g of 3.0-generation carboxyl-terminated polyamidoamine, 7 g of silica supported, 4 g of organic bentonite, 0.2 g of zinc oxide, 2.5 g of cross-linking agent, 1.2 g of triallyl isocyanurate, 2.5 g of antioxidant 4010, 1.5 g of stearic acid, and 2.5 g of triethylene glycol diisooctoate.
[0047] The cross-linking agent is composed of sulfur and bis(tert-butylperoxyisopropyl)benzene in a mass ratio of 11:6.
[0048] The silica supported is prepared by the following specific operations: Add 1.2 g of zirconium acetate and 1.8 g of yttrium acetate to 30 g of deionized water and stir evenly, add 4 g of urea thereto, stir at a temperature of 82 °C for 9 h, centrifuge, wash, dry in vacuum, add it to 30 g of an ethanol aqueous solution with a mass fraction of 55%, add 1.5 g of saturated ammonia water thereto and stir evenly, add 2.5 g of tetraethyl orthosilicate thereto under stirring, stir at a temperature of 42 °C for 12 h, centrifuge, wash, and dry in vacuum.
[0049] The preparation method of the above rubber composite material for high-performance tires includes the following steps:
[0050] S1. Add the muscovite powder to 70 g of an ethanol aqueous solution with a mass fraction of 55% and perform ultrasonic treatment for 80 min at an ultrasonic frequency of 12 kHz, add saturated ammonia water thereto and perform ultrasonic treatment for 80 min at an ultrasonic frequency of 9 kHz, add tetraethyl orthosilicate thereto under stirring and perform ultrasonic treatment for 80 min at an ultrasonic frequency of 9 kHz, let it stand for 3 h, filter, wash with deionized water, dry in vacuum, and grind through a 100-mesh sieve; add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamidoamine, and stir at a temperature of 77 °C for 80 min at a stirring speed of 180 r / min to obtain pretreated silicate;
[0051] S2. Mix the pretreated silicate, silica supported, organic bentonite, zinc oxide, triallyl isocyanurate, and antioxidant 4010, and stir at a speed of 100 r / min for 18 min to obtain a mixed material;
[0052] S3. Put nitrile rubber, styrene-butadiene rubber and the mixture into a Banbury mixer and knead for 12 min at a kneading temperature of 85 °C and a Banbury mixer speed of 80 r / min. Add a crosslinking agent thereto and knead for 80 min at 175 °C to obtain a kneaded material.
[0053] S4. Cool the kneaded material to 125 °C, add stearic acid and triethylene glycol diisooctoate in sequence and plasticize for 15 min, then transfer to an open mill to produce sheets.
[0054] Example 4: A rubber composite for high-performance tires, the raw materials of which include: 90 g of nitrile rubber, 15 g of styrene-butadiene rubber, 18 g of muscovite powder, 1.3 g of saturated ammonia water, 9 g of tetraethyl orthosilicate, 7 g of amino-terminated liquid nitrile rubber, 4 g of graphene oxide, 1.3 g of 3.0-generation carboxyl-terminated polyamidoamine, 9 g of silica-supported, 2 g of organic bentonite, 0.8 g of zinc oxide, 1.5 g of crosslinking agent, 1.8 g of N,N'-m-phenylene bismaleimide, 1.5 g of antioxidant TMQ, 2.5 g of stearic acid, and 1.5 g of triethylene glycol diisooctoate.
[0055] The crosslinking agent is composed of sulfur and dicumyl peroxide in a mass ratio of 7:2.
[0056] The silica-supported is prepared by the following specific operations: Add 1.8 g of zirconium acetate and 1.2 g of yttrium acetate to 40 g of deionized water and stir evenly. Add 2 g of urea thereto, stir at 88 °C for 7 h, centrifuge, wash, dry in vacuum, add to 40 g of an ethanol aqueous solution with a mass fraction of 45%, add 2.5 g of saturated ammonia water thereto and stir evenly. Add 1.5 g of tetraethyl orthosilicate thereto under stirring and stir at 48 °C for 8 h, centrifuge, wash, and dry in vacuum.
[0057] The preparation method of the above rubber composite for high-performance tires includes the following steps:
[0058] S1. Add muscovite powder to 90 g of an ethanol aqueous solution with a mass fraction of 45% and perform ultrasonic treatment for 100 min at an ultrasonic frequency of 6 kHz. Add saturated ammonia water thereto and perform ultrasonic treatment for 100 min at an ultrasonic frequency of 6 kHz. Add tetraethyl orthosilicate thereto under stirring and perform ultrasonic treatment for 100 min at an ultrasonic frequency of 6 kHz. Let stand for 5 h, filter, wash with deionized water, dry in vacuum, and grind through a 100-mesh sieve. Add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamidoamine, and stir at 73 °C for 100 min at a stirring speed of 120 r / min to obtain a pretreated silicate.
[0059] S2. Mix the pretreated silicate, silica-supported, organic bentonite, zinc oxide, N,N'-m-phenylene bismaleimide, and antioxidant TMQ, and stir at a speed of 160 r / min for 12 min to obtain a mixed material;
[0060] S3. Put the nitrile rubber, styrene-butadiene rubber, and the mixed material into a mixer and knead for 18 min at a kneading temperature of 75 °C and a mixer speed of 120 r / min. Add a crosslinking agent and knead at a temperature of 165 °C for 100 min to obtain a kneaded material;
[0061] S4. Cool the kneaded material to 115 °C, add stearic acid and triethylene glycol diisooctate in sequence and plasticize for 25 min, then transfer to an open mill to produce sheets.
[0062] Example 5: A rubber composite for high-performance tires, the raw materials of which include: 80 g of nitrile rubber, 20 g of styrene-butadiene rubber, 15 g of muscovite powder, 1.5 g of saturated ammonia water, 8 g of tetraethyl orthosilicate, 8 g of amino-terminated liquid nitrile rubber, 3 g of graphene oxide, 1.5 g of 3.0-generation carboxyl-terminated polyamidoamine, 8 g of silica-supported, 3 g of organic bentonite, 0.5 g of zinc oxide, 2 g of crosslinking agent, 1.5 g of triallyl isocyanurate, 2 g of antioxidant DNP, 2 g of stearic acid, and 2 g of triethylene glycol diisooctate.
[0063] The crosslinking agent is composed of sulfur and bis(tert-butylperoxyisopropyl)benzene in a mass ratio of 5:2.
[0064] The silica-supported is prepared by the following specific operations: Add 1.5 g of zirconium acetate and 1.5 g of yttrium acetate to 35 g of deionized water and stir evenly. Add 3 g of urea thereto, stir at a temperature of 85 °C for 8 h, centrifuge, wash, vacuum dry, add to 35 g of an ethanol aqueous solution with a mass fraction of 50%, add 2 g of saturated ammonia water thereto and stir evenly, add 2 g of tetraethyl orthosilicate thereto under stirring, stir at a temperature of 45 °C for 10 h, centrifuge, wash, and vacuum dry.
[0065] The preparation method of the above rubber composite for high-performance tires includes the following steps:
[0066] S1. Add the muscovite powder to 80 g of an ethanol aqueous solution with a mass fraction of 50% and perform ultrasonic treatment for 90 min at an ultrasonic frequency of 9 kHz. Add saturated ammonia water thereto and perform ultrasonic treatment for 90 min at an ultrasonic frequency of 7.5 kHz. Add tetraethyl orthosilicate thereto under stirring and perform ultrasonic treatment for 90 min at an ultrasonic frequency of 7.5 kHz. Let stand for 4 h, filter, wash with deionized water, vacuum dry, and grind through a 100-mesh sieve; Add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamidoamine, and stir at a temperature of 75 °C for 90 min at a stirring speed of 150 r / min to obtain a pretreated silicate;
[0067] S2. Mix the pretreated silicate, silica-supported, organic bentonite, zinc oxide, triallyl isocyanurate, and antioxidant DNP, and stir at a speed of 120 r / min for 15 min to obtain a mixed material.
[0068] S3. Put the nitrile rubber, styrene-butadiene rubber, and the mixed material into an internal mixer and knead for 15 min. The kneading temperature is 80 °C, and the speed of the internal mixer is 100 r / min. Add a crosslinking agent and knead at 170 °C for 90 min to obtain a kneaded material.
[0069] S4. Cool the kneaded material to 120 °C, add stearic acid and triethylene glycol diisooctate in sequence and plasticize for 20 min, then transfer to an open mill to produce sheets.
[0070] Comparative Example 1: A rubber composite for high-performance tires, the raw materials of which include: 80 g of nitrile rubber, 20 g of styrene-butadiene rubber, 15 g of muscovite powder, 1.5 g of saturated ammonia water, 8 g of tetraethyl orthosilicate, 8 g of amino-terminated liquid nitrile rubber, 3 g of graphene oxide, 1.5 g of 3.0-generation carboxyl-terminated polyamidoamine, 8 g of silica-supported, 3 g of organic bentonite, 0.5 g of zinc oxide, 2 g of crosslinking agent, 1.5 g of triallyl isocyanurate, 2 g of antioxidant DNP, 2 g of stearic acid, and 2 g of triethylene glycol diisooctate.
[0071] The crosslinking agent is composed of sulfur and bis(tert-butylperoxyisopropyl)benzene in a mass ratio of 5:2.
[0072] The silica-supported is prepared by the following specific operations: Add 1.5 g of zirconium acetate and 1.5 g of yttrium acetate to 35 g of deionized water and stir evenly. Add 3 g of urea thereto, stir at 85 °C for 8 h, centrifuge, wash, and vacuum dry. Then add it to 35 g of an ethanol aqueous solution with a mass fraction of 50%. Add 2 g of saturated ammonia water thereto and stir evenly. Add 2 g of tetraethyl orthosilicate thereto under stirring and stir at 45 °C for 10 h, centrifuge, wash, and vacuum dry.
[0073] The preparation method of the above rubber composite for high-performance tires includes the following steps:
[0074] S1. Add tetraethyl orthosilicate to 80 g of an ethanol aqueous solution with a mass fraction of 50% and perform ultrasonic treatment for 90 min. The ultrasonic frequency is 9 kHz. Add saturated ammonia water thereto and perform ultrasonic treatment for 90 min. The ultrasonic frequency is 7.5 kHz. Let it stand for 4 h, filter, wash with deionized water, vacuum dry, add muscovite powder and mix evenly, and grind through a 100-mesh sieve. Add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamidoamine, and stir at 75 °C for 90 min. The stirring speed is 150 r / min to obtain a pretreated silicate.
[0075] S2. Mix the pretreated silicate, silica-loaded, organic bentonite, zinc oxide, triallyl isocyanurate, and antioxidant DNP, and stir at a speed of 120 r / min for 15 min to obtain a mixture.
[0076] S3. Put the nitrile rubber, styrene-butadiene rubber, and the mixture into a kneader and knead for 15 min at a kneading temperature of 80 °C and a kneader speed of 100 r / min. Add a crosslinking agent and knead at 170 °C for 90 min to obtain a kneaded material.
[0077] S4. Cool the kneaded material to 120 °C, add stearic acid and triethylene glycol diisooctylate in sequence and plasticize for 20 min, then transfer to an open mill to make sheets.
[0078] Comparative Example 2: A rubber composite for high-performance tires, the raw materials of which include: 80 g of nitrile rubber, 20 g of styrene-butadiene rubber, 15 g of muscovite powder, 1.5 g of saturated ammonia water, 8 g of tetraethyl orthosilicate, 8 g of amino-terminated liquid nitrile rubber, 3 g of graphene oxide, 1.5 g of 3.0-generation carboxyl-terminated polyamidoamine, 8 g of silica-loaded, 3 g of organic bentonite, 0.5 g of zinc oxide, 2 g of crosslinking agent, 1.5 g of triallyl isocyanurate, 2 g of antioxidant DNP, 2 g of stearic acid, and 2 g of triethylene glycol diisooctylate.
[0079] The crosslinking agent is composed of sulfur and bis(tert-butylperoxyisopropyl)benzene in a mass ratio of 5:2.
[0080] The silica-loaded is prepared by the following specific operations: Add 1.5 g of zirconium acetate and 1.5 g of lanthanum acetate to 35 g of deionized water and stir evenly. Add 3 g of urea thereto, stir at 85 °C for 8 h, centrifuge, wash, and vacuum dry. Then add it to 35 g of an ethanol aqueous solution with a mass fraction of 50%. Add 2 g of saturated ammonia water thereto and stir evenly. Add 2 g of tetraethyl orthosilicate thereto under stirring and stir at 45 °C for 10 h, centrifuge, wash, and vacuum dry.
[0081] The preparation method of the above rubber composite for high-performance tires includes the following steps:
[0082] S1. Add muscovite powder to 80 g of an ethanol aqueous solution with a mass fraction of 50% and ultrasonically treat it for 90 min at an ultrasonic frequency of 9 kHz. Add saturated ammonia water thereto and ultrasonically treat it for 90 min at an ultrasonic frequency of 7.5 kHz. Add tetraethyl orthosilicate thereto under stirring and ultrasonically treat it for 90 min at an ultrasonic frequency of 7.5 kHz. Let it stand for 4 h, filter, wash with deionized water, dry in vacuum, and grind through a 100-mesh sieve. Add terminal amino liquid nitrile rubber, graphene oxide, and terminal carboxyl polyamidoamine, and stir at 75 °C for 90 min at a stirring speed of 150 r / min to obtain pretreated silicate;
[0083] S2. Mix the pretreated silicate, silica-supported, organic bentonite, zinc oxide, triallyl isocyanurate, and antioxidant DNP, and stir at a speed of 120 r / min for 15 min to obtain a mixture;
[0084] S3. Put nitrile rubber, styrene-butadiene rubber, and the mixture into a mixer and knead for 15 min at a kneading temperature of 80 °C and a mixer speed of 100 r / min. Add a crosslinking agent thereto and knead at 170 °C for 90 min to obtain a kneaded material;
[0085] S4. Cool the kneaded material to 120 °C, add stearic acid and triethylene glycol diisooctoate in sequence and plasticize for 20 min, and transfer to an open mill to produce sheets.
[0086] Comparative Example 3: A rubber composite for high-performance tires, the raw materials of which include: 80 g of nitrile rubber, 20 g of styrene-butadiene rubber, 15 g of muscovite powder, 1.5 g of saturated ammonia water, 8 g of tetraethyl orthosilicate, 8 g of terminal amino liquid nitrile rubber, 3 g of graphene oxide, 1.5 g of 3.0-generation terminal carboxyl polyamidoamine, 8 g of silica-supported, 3 g of organic bentonite, 0.5 g of zinc oxide, 2 g of crosslinking agent, 1.5 g of triallyl isocyanurate, 2 g of antioxidant DNP, 2 g of stearic acid, and 2 g of triethylene glycol diisooctoate.
[0087] The crosslinking agent is composed of sulfur and bis(tert-butylperoxyisopropyl)benzene in a mass ratio of 5:2.
[0088] The silica-supported is prepared by the following specific operation: Add 1.5 g of zirconium acetate and 1.5 g of yttrium acetate to 35 g of deionized water and stir evenly. Add 3 g of urea thereto and stir at 85 °C for 8 h. Centrifuge, wash, dry in vacuum, add to 35 g of an ethanol aqueous solution with a mass fraction of 50%, add 2 g of saturated ammonia water thereto and stir evenly, add 2 g of tetraethyl orthosilicate thereto under stirring, and stir at 45 °C for 10 h. Centrifuge, wash, and dry in vacuum.
[0089] The preparation method of the above rubber composite for high-performance tires includes the following steps:
[0090] S1. Add muscovite powder to 80 g of an ethanol aqueous solution with a mass fraction of 50% and perform ultrasonic treatment for 90 min at an ultrasonic frequency of 9 kHz. Add saturated ammonia water thereto and perform ultrasonic treatment for 90 min at an ultrasonic frequency of 7.5 kHz. Add tetraethyl orthosilicate thereto under stirring and perform ultrasonic treatment for 90 min at an ultrasonic frequency of 7.5 kHz. Let it stand for 4 h, filter, wash with deionized water, dry in vacuum, and grind through a 100-mesh sieve. Add terminal amino liquid nitrile rubber and terminal carboxyl polyamidoamine, and stir at 75 °C for 90 min at a stirring speed of 150 r / min to obtain pretreated silicate;
[0091] S2. Mix the pretreated silicate, silica-supported, organic bentonite, graphene oxide, zinc oxide, triallyl isocyanurate, and antioxidant DNP, and stir at a speed of 120 r / min for 15 min to obtain a mixture;
[0092] S3. Put nitrile rubber, styrene-butadiene rubber, and the mixture into a mixer and knead for 15 min at a kneading temperature of 80 °C and a mixer speed of 100 r / min. Add a crosslinking agent thereto and knead at 170 °C for 90 min to obtain a kneaded material;
[0093] S4. Cool the kneaded material to 120 °C, add stearic acid and triethylene glycol diisooctate in sequence and plastify for 20 min, and then transfer to an open mill to produce sheets.
[0094] Perform performance tests on the composite materials obtained in Example 5 and Comparative Examples 1-3 as follows:
[0095] (1) Refer to GB / T 528-2009 "Rubber, vulcanized or thermoplastic - Determination of tensile stress-strain properties" to measure the tensile strength, 100% modulus at specified elongation, and elongation at break of each group of specimens, and the tensile speed is 500 ± 5 mm / min;
[0096] (2) Refer to GB / T 529-2008 "Rubber, vulcanized or thermoplastic - Determination of tear strength (trouser, right-angle and crescent test pieces)" to measure the tear strength of each group of specimens, and each specimen is a right-angle specimen.
[0097] As Figure 1 and Figure 2 shown, the tensile strength, 100% modulus at specified elongation, elongation at break, and tear strength of the composite material obtained in Example 5 are all the highest, superior to those of Comparative Examples 1-3 (P < 0.05).
[0098] The dry friction and wear tests were carried out on the composite materials obtained in Example 5 and Comparative Examples 1-3, and the test conditions were as follows: (1) the load was 60 N and the sliding speed was 70 mm / s, (2) the load was 140 N and the sliding speed was 300 mm / s; the friction coefficients and wear rates of each group of specimens were measured.
[0099] As Figure 3 and Figure 4 shown, when the specimens of each group were compared longitudinally, as the load increased and the sliding speed became faster, the friction coefficients and wear rates of each group of specimens decreased instead; but when the specimens of each group were compared transversely, the friction coefficients and wear rates of the composite materials obtained in Example 5 were always the lowest, better than those of Comparative Examples 1-3 (P < 0.05).
[0100] The applicant believes that: this is because the nano-silica is loaded on the layered silicate mineral in the present invention. Not only is the nano-silica not easy to fall off, but it also has excellent dispersibility with the terminal amino liquid nitrile rubber, graphene oxide, and terminal carboxyl polyamidoamine, and the binding strength between them is high. Compared with directly adding the layered silicate mineral, the product not only has excellent tear resistance, but also has excellent definite elongation stress at a lower deformation (100%). At the same time, in the present invention, zirconium acetate and yttrium acetate are compounded and doped, and nano-silica is loaded on its surface and compounded with the pretreated silicate. On the premise of avoiding adding carbon black, the reinforcing effect is excellent, and at the same time, the interfacial action between silica and rubber can be improved, so as to promote the good dispersion of silica in rubber, form multiple cross-linking sites between the molecular chains of nitrile rubber and styrene-butadiene rubber, endow the product with excellent wear resistance and tear resistance, and have better durability than ordinary tires.
[0101] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art within the technical scope disclosed by the present invention, according to the technical solution and inventive concept of the present invention, makes equivalent substitutions or changes, and should be covered by the protection scope of the present invention.
Claims
1. A rubber composite material for high-performance tires, characterized in that: The raw materials include, by mass: 50-100 parts of nitrile rubber, 10-30 parts of styrene-butadiene rubber, 10-20 parts of silicate mineral powder, 1-2 parts of saturated ammonia water, 5-10 parts of tetraethyl orthosilicate, 5-10 parts of amino-terminated liquid nitrile rubber, 1-5 parts of graphene oxide, 1-2 parts of carboxyl-terminated polyamidoamine, 5-10 parts of loaded silicon dioxide, 1-5 parts of organic bentonite, 0.1-1 parts of zinc oxide, 1-3 parts of crosslinking agent, 1-2 parts of vulcanization accelerator, 1-3 parts of antioxidant, 1-3 parts of stearic acid and 1-3 parts of dispersant. The loaded silica is prepared by the following specific operation: adding zirconium acetate and yttrium acetate to water and stirring evenly, adding urea thereto, stirring at 80-90° C. for 5-10 hours, centrifuging, washing, vacuum drying, adding to ethanol aqueous solution, adding saturated ammonia water thereto and stirring evenly, adding ethyl orthosilicate thereto under stirring, stirring at 40-50° C. for 5-15 hours, centrifuging, washing, and vacuum drying; Pretreated silicate is prepared by using silicate mineral powder, saturated ammonia water, tetraethyl orthosilicate, amino-terminated liquid nitrile rubber, graphene oxide and carboxyl-terminated polyamide amine. The specific operation is as follows: add the silicate mineral powder to an ethanol aqueous solution and ultrasonically treat it for 1-2 hours, add saturated ammonia water thereto and ultrasonically treat it for 1-2 hours, add tetraethyl orthosilicate thereto under stirring and ultrasonically treat it for 1-2 hours, let it stand for 2-6 hours, filter, wash, vacuum dry, grind and sieve; add amino-terminated liquid nitrile rubber, graphene oxide and carboxyl-terminated polyamide amine, stir at 70-80°C for 1-2 hours to obtain pretreated silicate.
2. The high performance tire rubber composite material according to claim 1, characterized in that: The silicate mineral powder is at least one of talc powder, muscovite powder and montmorillonite powder.
3. The high performance tire rubber composite material according to claim 1, characterized in that: The cross-linking agent includes sulfur and organic peroxide, and the mass ratio of sulfur to organic peroxide is 2-3:0.5-1.5; The organic peroxide is diisopropylbenzene peroxide or / and bis(tert-butylperoxyisopropyl)benzene.
4. The high performance tire rubber composite material according to claim 1, characterized in that: The vulcanization accelerator is triallyl isocyanurate or / and N,N'-m-phenylene bismaleimide.
5. The high performance tire rubber composite material according to claim 1, characterized in that: The dispersant is sodium methylene dinaphthalene sulfonate or triethylene glycol diisooctanoate.
6. The high performance tire rubber composite material according to claim 1, characterized in that: The antioxidant is at least one of antioxidant BLE, antioxidant 445, antioxidant 4010, antioxidant DNP, and antioxidant TMQ.
7. The high performance tire rubber composite material according to claim 1, characterized in that: The mass ratio of zirconium acetate, yttrium acetate, saturated ammonia water and tetraethyl orthosilicate is 1-2:1-2:1-3:1-3.
8. A method for preparing the rubber composite material for high-performance tires according to any one of claims 1 to 7, characterized in that: The steps include: S1. Add silicate mineral powder to ethanol aqueous solution and ultrasonically treat for 1-2h, add saturated ammonia water and ultrasonically treat for 1-2h, add ethyl orthosilicate and ultrasonically treat for 1-2h under stirring, let stand for 2-6h, filter, wash, vacuum dry, grind and sieve; add amino-terminated liquid nitrile rubber, graphene oxide, and carboxyl-terminated polyamide amine, stir at 70-80°C for 1-2h to obtain pretreated silicate; S2, mixing the pretreated silicate, loaded silica, organic bentonite, zinc oxide, vulcanization accelerator, and antioxidant to obtain a mixture; S3, mixing the nitrile rubber, styrene butadiene rubber and the mixed material for 10-20 minutes at a mixing temperature of 70-90° C., adding a crosslinking agent thereto, and mixing at 160-180° C. for 1-2 hours to obtain a mixed material; S4. Cool the mixed material to 110-130°C, add stearic acid and dispersant in sequence, and plasticize for 10-30 minutes to form sheets.
9. The method for preparing the rubber composite material for high-performance tires according to claim 8, characterized in that: In S1, the frequency of ultrasonic treatment after the silicate mineral powder is added to the ethanol aqueous solution is 5-15 kHz, the frequency of ultrasonic treatment after adding saturated ammonia water is 5-10 kHz, and the frequency of ultrasonic treatment after adding tetraethyl orthosilicate is 5-10 kHz.
Citation Information
Patent Citations
ZrO2-SiO2 compound oxides, its preparation method and application
CN101007268A
Novel method for crosslinking acrylonitrile butadiene by supported transient metal
CN101486800A
Cited By
High-performance wear-resistant tire composite material and preparation method thereof
CN121378909A